CEREBROPROTECTIVE ACTIVITY OF NEW DERIVATIVES OF PIRIMIDINE4 1H ONE PIR9 AND PIR10 IN IRREVERSIBLE OCCLUSION OF THE COMMON CAROTID ARTERY - A. V. Voronkov; N. B. Shabanova; I. P. Kodonidi; I. S. Shatalov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
The frequency of cerebral hemodynamics disorders remains one of the most relevant problems in the modern world. Disorders of brain blood supply lead to high disability of the population, director disability, as well as fatal outcomes. There is an extensive group of drugs that contribute to the treatment and prevention of cerebrovascular disorders, however, they do not fully meet the requirements of practitioners. In this regard, the task of purposeful search and study of new substances with anti-ischemic activity becomes a task of experimental pharmacology. The aim of this work is to study the cerebroprotective activity of the new derivatives of Pirimidine-4-(1H)-OHA PIR-9 and PIR-10 in irreversible occlusion of the common carotid artery. Materials and methods. The study was carried out on 120 male rats of the Wistar line, weighing 200-220 g, divided into 6 equal groups. The investigated substances - PIR-9 and PIR-10 (50 mg / kg), vinpocetine (3.2 mg / kg), cinnarizine (5.6 mg / kg), a suspension of puri ed water with Tween-80 - were injected intraperitoneally for 10 days , as well as an hour before the operation. Global cerebral ischemia was modeled under chloral hydrate anesthesia (350 mg / kg) by dressing the common carotid arteries. 24 hours after the ischemia model, the survival, behavioral activity, cognitive and mnestic functions as well as certain metabolic disorders were evaluated. Results and discussion. In the experimental study of cerebroprotective action of the compounds PIR-9 and PIR-10 (derivatives of pyrimidine-4-(1H)-OHA) a decrease in neurological, locomotor, tentative research, cognitive, mental disorders in the background of ligation of common carotid artery was established. In addition, after preventive administration of the studied substances PIR-9 and PIR-10, there was an improvement in the processes of energy metabolism in the postischemic period. Conclusion. As for the cerebroprotective activity, the experimental substances (PIR-and PIR 9-10) were superior to the reference preparation of Vinpocetine and were comparable with Cinnarizine. That proves the feasibility of further study of derivatives of pyrimidine-4(1H)-ONA as potential anti-ischemic agents.